Research on performance measurement and simulation of civil air defense PPP projects using system dynamics - Tang, Lingyi; Yue, Yibo; Xiahou, Xiaer; Tang, Shi; Li, Qiming (Journal of Civil Engineering and Management, 2021)
Public Private Partnership (PPP) mode is increasingly applied in civil air defense (CAD) projects to improve project quality and reduce the government’s financial pressure. Because CAD project has different attributes during wartime and peacetime states, it’s necessary to comprehensively consider the project performance under different states to conduct scientific performance measurement. This paper focuses on the process of construction, operation, and handover of CAD PPP project to construct a unified project performance measurement indicator system, then a system dynamics (SD) model is established to carry out dynamic performance measurement and simulation of CAD PPP project under different social states respectively. A case study is conducted to verify the effectiveness of the proposed SD model, model validation, sensitivity analysis and result analysis were included as well. The study result can make the project performance management of CAD PPP more scientific and reasonable, and help decision-makers to formulate effective performance improvement strategies. It’s found out that government plays an important role in CAD PPP projects, when resources are limited, the government should give priority to measures such as reducing tax rates and increasing subsidies to ensure project benefits. The research methods can also provide reference for performance measurement of other PPP projects.